THE ROLE OF INTELLECTUAL PROPERTY IN DRIVING INNOVATION AND THE CREATIVE ECONOMY (European Journal of Economics, Finance and Business Development, 2025)
This article examines the role of intellectual property in the development of the creative economy and in fostering innovation. Based on international experience, official statistical data, and modern methodological approaches, the mechanisms for protecting intellectual property are analyzed, and contemporary challenges along with potential solutions for Uzbekistan’s institutional framework are proposed.